성인 영어학습자의 세계영어에 관한 인식과 영어 말하기 불안 - 김은영; 김현옥 (영어학, 2018)
The present study investigates EFL adult learners’ perceptions about World Englishes and their relationship to speaking anxiety based on the following three research questions: 1) What attitudes and perceptions do Korean EFL adults have toward World Englishes? and how do background variables influence their perceptions?; 2) To what extent do the levels of speaking anxiety vary with different interlocuters, i.e., native versus non-native speakers and relate to the amount of contact; and 3) How their perceptions toward World Englishes affect their language anxiety? A survey questionnaire was completed by a total of 110 adult EFL learners. Results indicate that 1) Korean adult learners have rather positive attitudes toward World Englishes, endorsing different varieties as a valid means for international communication, 2) their exposure to World Englishes positively influences their attitudes toward different varieties of English, and 3) they tend to experience higher levels of anxiety when they interact with native speakers than non-native speakers in English, and 4) their perceptions toward non-standard English are negatively related to the levels of language anxiety. The findings suggest that Korean ELT teachers and professionals in materials development and testing services should take into account the value and status of World Englishes to cultivate the Korean learners’ intercultural competence in the era of globalization.
Keywords: World Englishes; lingua franca; standard English; speaking anxiety; affective factors